Persekitaran bandar lestari untuk kesejahteraan komuniti - Abdul Samad Hadi; Shaharudin Idrus; Abdul Hadi Harman Shah (Environmental Management Society, Malaysia, 2004)
This paper argues that the preparation of a good environment for urban wellbeing is directly related to efforts to develop urban sustainability. The concept of urban sustainability is matched with the concept of sustainable development which tries to achieve economic growth, while protecting the physical environment to generate urban socio-economic development. However, an urban area becomes unsustainable due to changes from natural environment to artificial environment. Therefore, a sustainable city attempts to achieve the economic growth to develop a good artificial urban environment for urban dweller wellbeing. The preparation of a good urban physical and social environment is matched with ‘utopia’ planning, which is planning for the best urban environment. This paper also argues that the way to create a good environment is by developing sustainable indicators. The indices can be used as tools to create urban sustainability as urban sustainability is still in the process stage and the final form does not exist